Kenaikan Kristus (Ascension) dan Implikasinya bagi Kehidupan Kristen - Josua Aritonang (Jurnal Teologi Amreta (ISSN: 2599-3100), 2025)
This article aims to respond to the neglect and oversimplification of the meaning of Christ’s ascension into heaven in contemporary contexts. This issue is of concern because there are still several churches in Indonesia that do not celebrate the moment of Christ’s ascension in their worship services. Moreover, sermons about the Ascension often come across as monotonous and overly apologetic, thus failing to provide a deep understanding of its meaning and theological significance. This study employs a method of critical theological reflection with a literature-based approach. The findings of the research reveal that the Ascension holds rich and profound spiritual meaning. Some key aspects identified include: the Ascension is not an ex-carnation; the Ascension as fulfillment; the movement of "descending" and "ascending"; the tension of being between present and absent; the concept of already but not yet (an eschatological hope); the notions of space and time; appreciation of the material world; and other related themes. It is hoped that this research can encourage a renewed understanding of the Ascension and offer a fresh perspective for the church and Christians in general.